Human quarantine: Toward reducing infectious pressure on chimpanzees at the Taï Chimpanzee Project, Côte d'Ivoire. Issue 1 (17th January 2017) - Grützmacher, Kim; Keil, Verena; Leinert, Vera; Leguillon, Floraine; Henlin, Arthur; Couacy‐Hymann, Emmanuel; Köndgen, Sophie; Lang, Alexander; Deschner, Tobias; Wittig, Roman M.; Leendertz, Fabian H.
Abstract : Due to their genetic relatedness, great apes are highly susceptible to common human respiratory pathogens. Although most respiratory pathogens, such as human respiratory syncytial virus (HRSV) and human metapneumovirus (HMPV), rarely cause severe disease in healthy human adults, they are associated with considerable morbidity and mortality in wild great apes habituated to humans for research or tourism. To prevent pathogen transmission, most great ape projects have established a set of hygiene measures ranging from keeping a specific distance, to the use of surgical masks and establishment of quarantines. This study investigates the incidence of respiratory symptoms and human respiratory viruses in humans at a human‐great ape interface, the Taï Chimpanzee Project (TCP) in Côte d'Ivoire, and consequently, the effectiveness of a 5‐day quarantine designed to reduce the risk of potential exposure to human respiratory pathogens. To assess the impact of quarantine as a preventative measure, we monitored the quarantine process and tested 262 throat swabs for respiratory viruses, collected during quarantine over a period of 1 year. Although only 1 subject tested positive for a respiratory virus (HRSV), 17 subjects developed symptoms of infection while in quarantine and were subsequently kept from approaching the chimpanzees, preventing potential exposure in 18 cases. Our results suggest that quarantine—in combination with monitoring for symptoms—is effective in reducing the risk of potential pathogen exposure. This research contributes to our understanding of how endangered great apes can be protected from human‐borne infectious disease.